Assessing & reporting on habits of mind - Costa, Arthur L.; Kallick, Bena. (Alexandria, VA : Association for Supervision and Curriculum Development, 2000)
Presents strategies and rubrics for assessing several "habits of mind" in students--such as persisting, managing impulsivity, and thinking flexibly--and explains how to teach parents and peer groups to use assessment tools as well as teach students to self-assess.
"ASCD Stock No. 100034"--T.p. verso.
Includes bibliographical references and index.
Professional
Keywords: Students -- Rating of -- United States; Thought and thinking -- Study and teaching -- United States; Students -- United States; Thought and thinking -- Study and teaching